Health Care Utilization and Associated Economic Burden of Postoperative Surgical Site Infection after Spinal Surgery with Follow-Up of 24 Months - Dietz, Nicholas; Sharma, Mayur; Adams, Shawn; Ugiliweneza, Beatrice; Wang, Dengzhi; Bjurström, Martin F; Karikari, Isaac; Drazin, Doniel; Boakye, Max (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Surgical site infection (SSI) may lead to vertebral osteomyelitis, diskitis, paraspinal musculoskeletal infection, and abscess, and remains a significant concern in postoperative management of spinal surgery. SSI is associated with greater postoperative morbidity and increased health care payments.Methods We conducted a retrospective analysis using MarketScan to identify health care utilization payments and risk factors associated with SSI that occurs postoperatively. Known patient- or procedure-related risk factors were searched across those receiving spine surgery who developed postoperative infection.Results A total of 33,061 patients who developed infection after spinal surgery were identified in Marketscan. Overall payments at 6 months, including index hospitalization for those with infection, were $53,573 and $46,985 for the cohort with no infection. At 24 months, the infection group had overall payments of $83,280 and $66,221 for no infection. Risk factors with largest effect size most likely to contribute to infection versus no infection were depression (4.6%), diabetes (3.7), anemia (3.3%), two or more levels (2.8%), tobacco use (2.2%), trauma (2.1%), neoplasm (1.8%), congestive heart failure (1.3%), instrumentation (1.1%), renal failure (0.9%), intravenous drug use (0.8%), and malnutrition (0.5%).Conclusions SSIs were associated with significant health care utilization payments at 24 months of follow-up. The following clinical and procedural risk factors appear to be predictive of postoperative SSI: depression, diabetes, anemia, two or more levels, tobacco use, trauma, neoplasm, congestive heart failure, instrumentation, renal failure, intravenous drug use, and malnutrition. Interpretation of modifiable and nonmodifiable risk factors for infection informs surgeons of expected postoperative course and preoperative risk for this most common and deleterious postoperative complication to spinal surgery.
Keywords: surgical site infection; spinal infection; wound infection; risk factors; spine surgery